Single Cross Hybrid Seed Production in maize - Mishra, Sheshnath; Kumar, Arvind; Jat, S L; Parihar, C M; Sharma, Vishwanath; Chikkappa, G K; Singh, A K (Indian Farming, 2017)
Single hybrid seed production involves crossing of a female parentwith a male parent having desired characteristics in isolated field.Among the various techniques of hybrid seed production, such assingle cross, double cross, three ways cross and top cross, the foremost (single cross) technique is mostly favoured by farmers in India, due to uniformity and high yield.